Z-plasty: a comparative study between theoretical and practical elongation - Flavia Carnovale Lima; Bruno Pierotti Lessio; Germano Andriguetto de Lima; Thiago Paoliello Alves do Amaral; Antonio Carlos Abramo (Revista Brasileira de Cirurgia Plástica)
INTRODUCTION: The study of the final elongation values produced by 45º, 60º, 75º, and 90º-angle z-plasties performed on the skin of the lower abdomen of fresh cadavers were compared with the theoretical mathematical data published in the literature. METHODS: Four z-plasties with 2-cm main and secondary branches each, and with 45º, 60º, 75º, and 90º angles were performed on the skin of the lower abdomen in 11 fresh cadavers to evaluate the final elongation produced. RESULTS: The mean elongation at their respective angles was lower than that found in the literature, with a p value of <0.01. CONCLUSION: The elongation values obtained from the present study showed a significant difference from the published values.